Virtual Network Computing- A Technique to Control Android Phones Remotely (International Journal of Engineering and Computer Science, 2014)
Virtual Network Computing (VNC) is popular tool for graphical desktop sharing system which is used to control another computer remotely. Multiple clients may connect to a VNC server at the same time. Popular uses for this technology include remote technical support and accessing files on one's work computer from one's home computer, or vice versa. It makes use of Remote Frame Buffer protocol (RFB). RFB is a simple protocol for remote access to Graphical User Interface. VNC is an ultra-thin client system which is based on a simple display protocol. It is platform-independent. With the help of VNC one can achieve mobile computing without requiring the user to carry any hardware. This paper proposes a new architecture for remote control and access of android mobile devices .Which allows sharing of displays between android mobile phone and computers. This should be done within Wi-Fi range irrespective of various platforms. The image of the desktop is compressed before transmission. A modified region algorithm is used to reduce the encoding time of screen image and increase the screen update rate. A number of video encoders are integrated into a prototype system